Timely Surgical Intervention Leads to Better Sustained Coverage after Reconstructive Hip Surgery in Patients with Cerebral Palsy - Renée Anne van Stralen; Dagmar Raymond Jacques Kempink; Alexandra Frederika Titulaer; Denise Eygendaal; Max Reijman; Jaap Johannes Tolk (MDPI AG, 2024)
Background: In up to 45-90% of non-ambulatory patients with cerebral palsy (CP), progressive hip migration can be observed. The goal of this study was to determine whether the implementation of a national hip surveillance guideline affected the outcome of hip reconstructions. Methods: We reviewed 48 primary hip reconstructions at a median follow-up of 4.4 years. Surgical outcome was evaluated based on complication rates and radiographic evaluation postoperatively and at follow-up. Radiographic measurements included the migration percentage (MP), head-shaft angle and acetabular index. The impact of preoperative MP, postoperative MP, tone management, Gross Motor Function Classification System (GMFCS) classification and age on MP at follow-up were examined using a mixed model analysis. Results: A decrease in preoperative MP was noted, from a median of 75.0% (2014) to 39.0% (2020). Lower preoperative MP showed a significant correlation to lower MP postoperatively (p = 0.012). Postoperative MP was a significant independent predictor of a lower MP at follow-up (p = 0.002). Conclusions: This study shows an improvement in the timing of hip reconstruction in patients with CP after implementation of the hip surveillance guideline. A reduction in preoperative MP resulted in improved postoperative outcomes. A lower postoperative MP was the most important predictor for sustained containment of the hip.